Analysis of usage statistics of content page services provided to academic staff members of the University of Colombo - Sritharan, T. (The Library, University of Colombo., 2020)
This study presents the analysis of the usage statistics of content page service provided to the academic staff members of University of Colombo. The content pages of 25 subscribed journals are forwarded to all the academic staff members of the Faculties of Law, Education, Management and Finance and Arts, once the journals are received by the periodicals section. Based on these content pages the academic staff can request articles. The number of articles requested by the academic staff members based on this service during the period from October 2019 to October 2020 were used as data for this study. The data were collected by analyzing the email records of the requests made by the academic staff. A separate register was also maintained to record the details of the articles forwarded, including the name of the requester, article details, department and the faculty. The objective of this study is to analyze the usage pattern of the service. The analysis of data depicts that the majority of the articles were requested from the Faculty of Arts (227 or 51%). Faculty of Management and Finance requested 89 (20%) articles during this period, the Faculty of Law requested 83 (19%) article sand the Faculty of Education requested 43 (10%) articles. During the months of May and June 2020, more number of articles (196) have been requested by the academic staff members. Articles from “Demography” (86) and journals subscribed from American Economic Association (63) were highly requested by the Department of Demography and the Department of Economics. This study recommends that since the content page service is provided only to the above four faculties stated in this study, and is acknowledged and extensively used (total number of 442 articles have been requested) by the staff members of these faculties as evident in the data provided in this study, expanding this service to the staff members of other faculties and the students would be beneficial. This study also recommends to send the content pages of all the subscribed journals. To increase the quality of the current content page services and to get the level of satisfaction on this service, a survey must be conducted among the academic staff members of University of Colombo.
Keywords: Content Page Services, Subscribed journals, Reference services, Usage statistics